Beyond the superordinate categories of “Gay Men” and “Lesbian Women”: Identification of gay and lesbian subgroups - McCutcheon, Jessica M.; Morrison, Melanie A. (Journal of Homosexuality, 2021)
Nation-wide opinion polls and social scientific studies indicate that evaluations of gay men and lesbian women have become increasingly favourable. These positive trends do not explain the widespread discrimination experiences being reported. To assist researchers in investigating attitudes towards gay and lesbian persons, the current research examines whether there are multiple “types” that are identifiable and salient. Two Canadian studies (Ns = 67 and 206) were conducted to establish the presence of gay and lesbian subgroups. Using subgroups generated by Study 1 participants, community and student sub-samples selected those they perceive to exist. Results indicated that, for gay men, the subgroups Drag Queen and Flamboyant emerged, as did Butch for lesbian women. Amongst students, Closeted and Feminine also emerged for gay men, as well as Feminist and Tomboy for lesbian women. These findings have implications for contemporary research on gay- and lesbian-related attitudes and the methodology used to assess them.
Keywords: amériques; canada; discipline; identités LGBTQIA2+; psychologie; ressource en ligne; régions géographiques; sciences humaines